2002
DOI: 10.1021/bi020286f
|View full text |Cite
|
Sign up to set email alerts
|

Monomeric Sarcosine Oxidase:  Role of Histidine 269 in Catalysis,

Abstract: Conservative mutation of His269 (to Asn, Ala, or Gln) does not-significantly affect the expression of monomeric sarcosine oxidase (MSOX), covalent flavinylation, the physicochemical properties of bound FAD, or the overall protein structure. Turnover with sarcosine and the limiting rate of the reductive half-reaction with L-proline at pH 8.0 are, however, nearly 2 orders of magnitude slower than that with with wild-type MSOX. The crystal structure of the His269Asn complex with pyrrole-2-carboxylate shows that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
59
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(65 citation statements)
references
References 21 publications
6
59
0
Order By: Relevance
“…The results show that Tyr317 in wild type enzyme does not act as the acceptor of the proton released upon substrate ionization. We have previously shown that ionization of the enzyme·L-proline complex is unaffected by mutation His269, the other possible active site base (3). Therefore, we conclude that L-proline itself is the ionizable group in the enzyme·substrate complex.…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…The results show that Tyr317 in wild type enzyme does not act as the acceptor of the proton released upon substrate ionization. We have previously shown that ionization of the enzyme·L-proline complex is unaffected by mutation His269, the other possible active site base (3). Therefore, we conclude that L-proline itself is the ionizable group in the enzyme·substrate complex.…”
Section: Discussionmentioning
confidence: 51%
“…Interestingly, the MSOX His269Asn mutant forms charge transfer complexes with MTA, PCA or the L-proline anion that exhibit spectral properties similar to those observed for the corresponding complexes with the Try317Phe mutant. A high resolution crystal structure of the His269Asn complex with PCA reveals small differences in the ligand binding mode as compared with wild type enzyme, suggesting that His269 plays a role in optimizing substrate binding (3). A similar role for Tyr317 would be consistent with the properties observed for the Phe mutant.…”
Section: Discussionmentioning
confidence: 60%
“…The resulting E280L mutant protein was completely inactive (Ͻ0.1 milliunits), indicating that Glu-280 is important for binding the substrate or for orienting it properly in the catalytic site. Interestingly, Glu-280 is equivalent to His-269 in B. subtilis MSOX, a residue believed to be important in the orientation of the substrate (29). Mutation of Arg-411 to Ser also resulted in an inactive FAOX-II.…”
Section: Resultsmentioning
confidence: 99%
“…In bacterial MSOX and most fungal sarcosine oxidases, a histidine (His-269 in the B. subtilis enzyme) is found in the position equivalent to Glu-280 in FAOX-II. This histidine plays an important role in substrate binding and positioning in the bacterial enzyme (29) and may, therefore, be considered as a signature residue for sarcosine oxidase activity. However, the Aspergillus oryzae enzyme does not have this histidine residue and has been reported to oxidize sarcosine (34).…”
Section: Resultsmentioning
confidence: 99%
“…Although several different mechanisms have been proposed, including hydride transfer, single electron transfer and polar mechanisms (38 -40), the mechanism underlying the monomeric sarcosine oxidase-catalyzed amine oxidation reaction remains unclear. Based on structural and site-directed mutagenesis studies, it has been proposed that Tyr 317 and His 269 in monomeric sarcosine oxidase, which are located close to the methyl group of the substrate, are not essential for catalysis but are important for optimizing substrate binding (39,40 A catalytic mechanism for hyperthermophilic LPDH was proposed by Monaghan et al (41), who studied the PDH1 homologue from P. furiosus (PRODH) and based their proposal on its preliminary crystal structure. Initially, ␤His 225 and ␤Tyr 251 , which are located close to the re-face of the flavin ring of FAD, were selected as potential candidates for the active-site base in P. furiosus PRODH, but site-directed mutagenesis studies revealed that these residues are not essential for catalysis.…”
Section: Structural Comparison Of Monomeric Apelpdh and Pdh1␤-mentioning
confidence: 99%